2021
DOI: 10.3389/fcvm.2021.695454
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Cardiovascular-Related Comorbidities in Different Adult-Onset Cancers and Related Risk Factors: Analysis of 10 Year Retrospective Data

Abstract: Introduction: Understanding the epidemiology of cardiovascular disease (CVD) related comorbidity is a key strategy for improving the outcomes of patients with cancer. Therefore, this study aimed to assess the distribution of cardiovascular comorbidities and cardiovascular risk factors (CVRF) among five cancer sites.Methods: This is a single-centered, cross-sectional study performed in Dalian, China. Between 2008 and 2018, all newly diagnosed cancer in the First Affiliated Hospital of Dalian Medical University,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…S4a) in our cohort of patients with LUAD. We next analyzed lipoprotein a in our cancer patients and found a significant inverse correlation between lipoprotein a 33 and the BMI in patients with advanced stadium of LUAD (Stage IV) (Supplementary Fig. S4b).…”
Section: Resultsmentioning
confidence: 98%
“…S4a) in our cohort of patients with LUAD. We next analyzed lipoprotein a in our cancer patients and found a significant inverse correlation between lipoprotein a 33 and the BMI in patients with advanced stadium of LUAD (Stage IV) (Supplementary Fig. S4b).…”
Section: Resultsmentioning
confidence: 98%
“…In 2006 and 2007, Chan et al delivered two publications reporting that patients with colorectal neoplasms suffered a higher prevalence of CAD than patients without colorectal neoplasms, while colorectal cancer was not significantly associated with CAD by multivariate logistic regression ( 4 , 16 ). In 2021, a retrospective study showed that lung, colorectal, gastric, breast, and thyroid cancer patients suffered from a relatively high prevalence of CVD, but this study did not include non-cancer patients ( 17 ). In our study, respiratory system, digestive system and urogenital system cancers were significantly associated with a higher risk of CAD compared with no cancer, with ORs of 1.981, 1.899 and 3.595, respectively (all p < 0.01), providing evidence for enhancing the prevention and screening of CAD in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to Li et al, the association between DM and the presence of CVDs was strong in breast, lung, colorectal, and gastric cancers [ 34 ]. Similarly, the present study demonstrated that BC, OC, and EC patients diagnosed with DM had a significantly increased risk for CVDs.…”
Section: Discussionmentioning
confidence: 99%